As elegias bordadas de Leonilson : expressões de afecto - Bonjour, Hugo Macieira (2017)
Considering Leonilson’s embroidery works, it’s perceived, in this article, his work as an intimate diary, and there’s a reflection about his synthesis capacity and sensibility while embroidering feelings and emotions, about the maximum exteriorization of the internal and about the melancholic lamentation that he imprints in his work